A New, Young, Low-Mass Spectroscopic Binary Without a Home. Issue Volume 10:Issue S314(2015) (November 2015) - Flagg, Laura S.; Shkolnik, Evgenya L.; Weinberger, Alycia J.; Bowler, Brendan P.; Kraus, Adam L.; Liu, Michael C.
Abstract: We have discovered that 2MASS 08355977-3042306 is an accreting K7, double-lined, spectroscopic binary younger than ~20 Myr. The age of a dispersed young star can best be determined if it is a member of a known young moving group. However, the three dimensional space velocities ( UVW ) we calculate using radial velocity measurements, proper motions, and plausible photometric distances make membership in any known young moving group unlikely.